Enhancing sustainability of ultra-high performance concrete utilizing high-volume waste glass powder. (December 2022) - Tahwia, Ahmed M.; Essam, Ahmed; Tayeh, Bassam A.; Elrahman, Mohamed Abd
Abstract: This paper investigates the effect of recycled waste glass powder (RWGP) and particle packing optimization on the performance of UHPC. RWGP was obtained by crushing and grinding waste glass and reaching a fineness close to that of cement to study its influence on UHPC performance. UHPC mixtures were designed by optimizing the binder system based on a modified Andreasen & Andersen (MAA) particle packing model with a distribution factor (q) of 0.22 in order to reduce the required cement content (450 kg/m 3 ). Seven different mixes have been designed, prepared, and tested with various RWGP content. Mechanical properties, durability, and microstructure of the developed concrete have been determined and evaluated. The results showed that the mixture with the inclusion of 10 % RWGP as a cement replacement achieves the highest mechanical properties at different ages. The interfacial transition zone (ITZ) is improved significantly when cement and quartz powder are replaced with RWGP. Moreover, the embodied CO2 index of RWGP50 % has been reduced to 3.7 kg/MPa/m 3, while the embodied CO2 for conventional UHPC ranged to 5.75 kg/MPa/m 3 . Based on the environmental and economic assessment, RWGP reduces UHPC production costs and harmful environmental impacts without sacrificing the mechanical, microstructure, and durability performance significantly. Through this assessment, the effectiveness of the use of 50 C/50RWGP has been demonstrated, providing wide opportunities for the continuous future development of Eco-UHPC